Kunst in opdracht 1999-2005 : kunstopdrachten begeleid door de kunstcel van de Vlaamse Bouwmeester. - Coessens, Piet; Laenen, Katrien; Lindmayr, Ulrike; Santens, Mark; Van Reeth, Bob (Brussel : Vlaams Bouwmeester Brussel, 2006)
't Jolle, Sven ; Van den Abeele, Michael ; Aerts, Jef ; Annerel, Stefan ; Barry, Orla ; Benhelima, Charif ; Benoît ; Bertrand, Lucile ; Biest, Francine Van Der ; Bijl, Guillaume ; Blondeel, Maria ; Van Bossche, Guy ; Braeckman, Dirk ; Van Breedam, Camiel ; Brey, Ricardo ; van den Broek, Koen ; Buren, Daniel ; De Busschère, Alec ; Van Caeckenbergh, Patrick ; Catrysse, Wim ; Charlier, Jacques ; Claessens, Martin ; Colson, Vaast ; de Cordier, Thierry ; Daems, Anne ; Dehaes, Ugo ; Deleu, Luc ; Delvoye, Wim ; Dendooven, Gerda ; Denicolai, Simona ; Dietvorst, Els ; Dillemans, Sam ; Downsbrough, Peter ; Duchateau, Hugo ; Dujourie, Lili ; Durham, Jimmie ; Evrard, David ; Vanden Eynde, Patrick ; Fink, Christoph ; François, Michel ; Garcia, Dora ; Geys, Jef ; Goiris, Geert ; Grimonprez, Johan ; Van Grunderbeek, Dimitri ; Harrison Studio ; Heymans, Bren ; Huycke, David ; Hyber, Fabrice ; Van Isacker, Philip ; Janssens, Ann Veronica ; Joliet, Ilse ; Kempenaers, Jan ; Van Kerckhoven, Anne-Mie ; De Keyser, Raoul ; Kieckens, Christian ; Kinoshita, Suchan ; Kirkeby, Per ; Konrad, Aglaia ; Lohaus, Bernd ; Lopez-Menchero, Emilio ; Maguire, Brian ; Vanden Meersch, Els ; Mertens, Nathalie ; Michels, Marjan ; Ney, Laurent ; Nijs, Lucas ; Van Obberghen, Vanessa ; Op de Beeck, Gert ; Op de Beeck, Hans ; Pereira Eires, Joaquim ; Pourbus, Pieter ; Provoost, Ivo ; Raveel, Roger ; Roberts, Perry ; Robijns, Gert ; Rogiers, Peter ; Rombouts, Guy ; Rooms, Veerle ; van Santen, Joost ; Van Snick, Philippe ; Stultiëns, Andrea ; Swennen, Walter ; Terlinden, Christophe ; Theys, Koen ; Thirion, Dominique ; Thomas, Stijn ; Tordoir, Narcisse ; Tuerlinckx, Joëlle ; Vanhaegenborgh, Eric ; Venlet, Richard ; Vercruysse, Jan ; Verhoeven, Gert ; Vermeire, Katrien ; Vermeyen, Steven ; etc.
boek